Sensitivity to microstimulation of somatosensory cortex distributed over multiple electrodes - Kim, Sungshin; Callier, Thierri; Tabot, Gregg A.; Tenore, Francesco V.; Bensmaia, Sliman J. (Frontiers in Systems Neuroscience, 2015)
Meaningful and repeatable tactile sensations can be evoked by electrically stimulating primary somatosensory cortex. Intracortical microstimulation (ICMS) may thus be a viable approach to restore the sense of touch in individuals who have lost it, for example tetraplegic patients. One of the potential limitations of this approach, however, is that high levels of current can damage the neuronal tissue if the resulting current densities are too high. The limited range of safe ICMS amplitudes thus limits the dynamic range of ICMS-evoked sensations. One way to get around this limitation would be to distribute the ICMS over multiple electrodes in the hopes of intensifying the resulting percept without increasing the current density experienced by the neuronal tissue. Here, we test whether stimulating through multiple electrodes is a viable solution to increase the dynamic range of ICMS-elicited sensations without increasing the peak current density. To this end, we compare the ability of non-human primates to detect ICMS delivered through one versus multiple electrodes. We also compare their ability to discriminate pulse trains differing in amplitude when these are delivered through one or more electrodes. We find that increasing the number of electrodes through which ICMS is delivered only has a marginal effect on detectability or discriminability despite the fact that 2-4 times more current is delivered overall. Furthermore, the impact of multielectrode stimulation (or lack thereof) is found whether pulses are delivered synchronously or asynchronously, whether the leading phase of the pulses is cathodic or anodic, and regardless of the spatial configuration of the electrode groups.